The Influence Of Celebrity Endorsers And The Attractiveness Of Advertising On The Purchase Decision Of Wardah Products On Tiktok Shop In Batam - Monika Fitri Sari Sianipar; Asron Saputra (LPPM Universitas Buddhi Dharma, 2025)
The more the digital world develops, the more diverse human needs become. The development of technology for the application of applications on smartphones is really efficient in meeting the needs of consumers. Tiktok as one of the most used applications around the world, takes advantage of this condition to be able to become a social e-commerce that can sell products through short videos. This convenience is experienced by consumers to buy goods, especially beauty products. Wardah is one of the beauty product brands that has a Halal label so that it attracts attention, especially Muslim women in Indonesia. The purpose of this study is to find out whether the variable Celebrity Endorser and attractiveness has an influence on the purchase decision of Wardah products on Tiktokshop in Batam. The method in this study uses a quantitative approach by examining as many as 204 respondents using the Non Probability Sampling and Purposive Sampling. Answers from respondents were received through a questionnaire that was distributed. The results of this study where the variable Celebrity Endorser exerts a significant influence on purchase decisions, attractiveness exerts a significant influence on purchase decisions. Celebrity endorsers and attraction have a significant influence simultaneously on purchasing decisions. Therefore, it can be concluded that celebrity endorsers and attractiveness have a significant positive influence on the decision to purchase Wardah products on the Tiktok Shop in Batam.